A Associação Cristã de Moços e experiências de escolarização da Educação Física no Brasil: sujeitos, ideias e práticas acemistas em circulação - Giovanna Camila da Silva (2017)
This study investigated the elements that constituted the Physical Education forged in the Young Mens Christian Association YMCA and that resounded in actions for the schooling of Brazilian Physical Education in the 1920s and 1930s. To do so, subjects trained as physical directors in the Association were put on the scene: Henry James Sims, YMCA missionary born in the United States who served at the Association's headquarters in Rio de Janeiro; Renato Eloy de Andrade, the Inspector of Physical Education of Minas Gerais; and Frederico Guilherme Gaelzer, who was also Inspector in Rio Grande do Sul and Director of Recreation Gardens in Porto Alegre. The proposed spatial and temporal cutbacks were justified by the activities carried out by Sims, Andrade and Gaelzer in those states and temporality, which had a close relationship with a systematization produced and disseminated by the YMCA. In the establishment of sources for this investigation, different archives were mobilized. Institutional documents were recruited at the Kautz Family YMCA Archives in Minneapolis, USA. From Montevideo, documents informing about the formation of secretaries and physical directors at the Technical Institute of the South American Federation of the Young Men's Christian Associations. Also in the institutional dimension, the official journal of the Association in Brazil was investigated in the Brazilian Federation of YMCAs and in the National Library. For the appropriation practices, documents that informed about the experiences of schooling of Physical Education in the different states investigated were sent. In Rio de Janeiro, from the collection of the Brazilian Association of Education, the documents referring to the Physical Education and Hygiene Section gained a centrality. For the state of Minas Gerais, the newspaper Minas Gerais, Official Organ of State Powers and the Journal of Teaching, important vehicles for the dissemination of educational policy and practices. In the Center for Memory of Sport in the School of Physical Education, Federal University of Rio Grande do Sul (UFRGS), the exploitation of the collection 'Leisure and Public Recreation'. In the construction of the plot, the creation of Protestantism in Brazil was considered as an aspect that made the insertion of the Association in the country possible and the elements that made up the systematization of Physical Education there were marked by protestant codes capable of justifying the moralization of customs, vocation to exercise a craft, the dimension of efficiency in practices, the rational use of physical exercises. This research evidenced that the contours for Physical Education forged in the Association did not take specificities for the school space, it was the dynamics of circulation of the subjects formed there that promoted modes of appropriations that participated in the schooling process of the school field. The Brazilian scenario of educational renewal was welcoming to the YMCA initiatives. The creation of specific organs responsible for inspecting, promoting and orienting the teaching of Physical Education in schools was also an incentive for the references organized, especially by Andrade and Gaelzer. In the process of appropriation, practices that reveal accession, reconfigurations and refusal to that established in the YMCA. Called to contribute to the debate and the initiatives related to the schooling of Physical Education, the investigated subjects carried out an exercise of recreation of senses, of necessary displacements. This research, when addressing the YMCA subjects and propositions, contemplated the intention of giving visibility to a systematization that, not belonging to the European universe of gymnastic methods, but, coming from the USA, also participated in the constitution of the Brazilian Physical Education.